OPTIMALISASI DIGITAL MARKETING PADA PENJUALAN PRODUK UMKM SEBAGAI BENTUK PEMBERDAYAAN PEREMPUAN DI DESA SINDANG KARYA, ANYER, BANTEN - Fitrianti, Rizqi; Endayani, Endayani; Zulfikar, Meiby; Kamilah, Fithrotul; Haque, Nuke Nurul; Shalsabila, Shalwa (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The right sales strategy can drive increased turnover. Digital marketing is the most effective media and strategy in expanding market reach. This is one way for a group of women in Sindang Karya Village - Anyer, Banten, to advance their products. Currently, the marketing is still conventional and simple. So that the turnover obtained has not been maximized, and product branding has not been achieved as a superior product. This devotion aims to utilize E-Commerse as an optimization of digital marketing in increasing sales of MSME products and processed home products managed by women’s groups in Sindang Karya Village, Anyer - Banten. As the role of women as the main actors in local economic activities, digital marketing strategies are expected to be the main driver in expanding market reach and increasing village community income. This research method uses a qualitative approach with data collection through observation, interviews, literature studies, and training conducted for 6 meetings by providing materials on digital marketing. The results showed that the application of appropriate digital marketing strategies, such as the use of social media, marketplaces, and attractive marketing content, can optimize the sales of local products and empower women in the area